Medida de deslocamentos e vibrações utilizando uma câmera digital como sensor sem contato - Leonardi, Danilo Montilha (2015)
This work presents the development of a technique for displacement measurements and vibration without contact, defined based on the variation of the pixel number of one or more reference points in images captured with the CCD type sensors (Charge Coupled Device) or CMOS (Complementary Metal Oxide Semiconductor). The captured image frames are analyzed and processed with the aid of mathematical tools of image processing such as thresholding in cutting, erosion and dilation, in order to highlight the reference point in the scene. The proposal is evaluated in static and dynamic experimental tests and compared to techniques conventional measurement of displacement, so that the static and dynamic tests are initially simple to validate the methodology, and in the end, this paper concludes with complex experience, where the presented methodology is used in extensometry studies and modal analysis based only on the response.